The Effect of Patient Safety Training on Patient Identification Compliance in the Radiology Unit at a Private Hospital in Medan - Sitepu, Nova Eininta; Tambunan, Dior (LLDIKTI Wilayah 1, 2024)
Patient Safety is an absence of preventable harm and reduction of risk unnecessary harm. Patient’s misidentifaction can be avoided through patient safety trainig. The study objective is to identify the effect of patient safety training on patient identification compliance in the Radiology Unit at a Private Hospital in Medan. The research method is Pre-Experimental design in one group pretest-posttest without control and 28 staffs as respondents with total sampling technique. The result showed that pretest Patient Identification Compliance on September was 67.9%, on October and November 2023 was decreased (64.3%) in the Radiology Unit. The Posttest Patient Identification Compliance after training on March 2024 (78.6%), April 2024 (85.7%), and May 2024 (92.9%) in the Radiology Unit. Patient Safety Incidents Based on Not Compliance of Patient Identification before Training on September – November 2023 were 10 findings and after Training on March – May 2024 were significantly reduced to 4 findings. The Wilcoxon test showed p-value 0.011 (? <0.05). The conclussion is that there was a meaningful effect of Patient Safety Training on Patient Identification Compliance. It is recommended for further researchers to add another variables such workload and staff’s competencies.